Analysis of the need for digital history teaching materials for the merdeka curriculum in senior high schools - Falah, Muhammad Fajrul; Andayani, Endang Sri; Hudiyanto, R Reza (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Changing from the 2013 curriculum to a Merdeka curriculum means that learning tools, including teaching materials, must be adjusted to appropriate learning outcomes and objectives of history subject. This research aims to determine the need for media, content, and language teaching materials. This research uses a qualitative study with a descriptive approach. Primary data sources were obtained from informants, namely Malang teachers and high school students, and observations in the field. The stages of data analysis are data reduction, data display, conclusion, and verification. The results show that the need for teaching materials in terms of media, namely: availability of wifi in schools and student internet quota, preferred font types are Calibri and Arial, preferred colors are bright colors, all students have smartphones with medium-high specifications, and videos and images in teaching materials must be explicit. There is a need for teaching materials in terms of content. Namely, the curriculum used is the Merdeka curriculum. Students prefer independent study, and some questions stimulate students to think historically. There is a need for teaching materials in terms of language. Namely, the language used as an introduction is Indonesian, and the language used must be easy for students to understand.